2022
DOI: 10.2147/ndt.s359620
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pain with Plasma C5a in Patients with Neuromyelitis Optica Spectrum Disorders During Remission

Abstract: Objective To investigate the association of pain with plasma C5a levels and other related inflammatory cytokines in neuromyelitis optica spectrum disorders (NMOSD) patients during remission. Participants and Methods NMOSD patients (n = 87) and healthy controls (HC; n = 44) were consecutively recruited between January 2017 and April 2018. Plasma complement 5 (C5), C5a, interleukin (IL)-6, tumor necrosis factor (TNF)-α, and IL-1β levels were detected. Visual Analogue Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The levels of C5a and C5 in plasma and cerebrospinal fluid are significantly increased in patients with major depression [11,77,78] Depression C3a-C3aR C3a can enhance calcium current and capsaicin-induced calcium inflow in dorsal root neurons of spinal cord [23]. TLQP-21 activates the C3aR1 receptor on the dorsal horn microglia of the spinal cord, which induced heat hyperalgesia and contributed to nerve injury-induced [73] SNI, CCI and SNL model [23] SNI model [73] Chronic pain and depression C3a-C3aR C3a-C3aR signaling pathway promotes M1 polarization of microglia and increases levels of hippocampal proinflammatory cytokines TNF-α and IL-1β [53].…”
Section: C5a-c5armentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of C5a and C5 in plasma and cerebrospinal fluid are significantly increased in patients with major depression [11,77,78] Depression C3a-C3aR C3a can enhance calcium current and capsaicin-induced calcium inflow in dorsal root neurons of spinal cord [23]. TLQP-21 activates the C3aR1 receptor on the dorsal horn microglia of the spinal cord, which induced heat hyperalgesia and contributed to nerve injury-induced [73] SNI, CCI and SNL model [23] SNI model [73] Chronic pain and depression C3a-C3aR C3a-C3aR signaling pathway promotes M1 polarization of microglia and increases levels of hippocampal proinflammatory cytokines TNF-α and IL-1β [53].…”
Section: C5a-c5armentioning
confidence: 99%
“…Research has demonstrated that the activation of complements, whether in the peripheral or CNS, contributes to the onset and progression of chronic pain. Tong et al [ 11 ] have examined the correlation between plasma levels of complement C5a and pain in individuals diagnosed with neuromyelitis optica spectrum disorders (NMOSD). They have revealed that patients with NMOSD had significantly elevated levels of plasma C5a.…”
Section: Main Bodymentioning
confidence: 99%
See 1 more Smart Citation